2016
DOI: 10.17305/bjbms.2016.1495
|View full text |Cite
|
Sign up to set email alerts
|

Unknown primary adenocarcinomas: a single-center experience

Abstract: This study aimed to elucidate the clinical and prognostic characteristics of a homogeneous group of patients with cancer of unknown primary (CUP). Between 1999 and 2014, CUP was diagnosed in 159 (1.3%) of 11,742 cancer patients at Trakya University Hospital (Edirne, Turkey). Ninety-seven (61%) of the 159 patients were retrospectively reviewed. Among these, 61 (62.8%) patients with adenocarcinoma were included in this study. The most frequently predicted primary tumor site was the lung (37.7%), and 59% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…This percentage is very similar to previous experiences from Western countries i.e. in previous reports, the origin of 25% -35% of metastatic liver cancers was unknown (11,12).…”
Section: Discussionsupporting
confidence: 91%
“…This percentage is very similar to previous experiences from Western countries i.e. in previous reports, the origin of 25% -35% of metastatic liver cancers was unknown (11,12).…”
Section: Discussionsupporting
confidence: 91%
“…It has the most aggressive behavior and is highly resistant to therapy. A better understanding of treatment and prognostic factors is possible by studying patients in homogenous subgroups with CUP [7].…”
Section: Reviewmentioning
confidence: 99%
“…A new therapeutic method based on molecular profiling associated with treatment benefit in 96% of the cases is proposed. Hence, expressing the wide-range of biomarker profiling using gene sequencing, immunohistochemistry, and in situ hybridization method identifies biomarkers [23]. In comprehensive genomic profiling, it is observed that there is at least one clinically appropriate genomic alteration in CUP that can influence the targeted therapy [24].…”
Section: Reviewmentioning
confidence: 99%
“…However, survival outcomes in CUP patients remain poor [21]. To ensure that patients with CUP can receive optimal care, identification of genetic abnormalities in addition to existing surveillance is urgently needed [2, 20, 22].…”
Section: Discussionmentioning
confidence: 99%